Integration and transnational practices of Filipinos in Iceland - Skaptadóttir, Unnur Dís (e-Migrinter, 2020)
Imelda is a fifty year old woman who moved to Iceland in the early 1990s. In the Philippines, she was a widow with three children having a difficult time making ends meet. She had a cousin living in Iceland who told her that she could arrange for her to come to work there, so Imelda left her children with her sister and mother and got a job in a rural Icelandic fish plant; she lived sparingly and sent what was left of her wages back to her family in the Philippines.